2013
DOI: 10.1139/gen-2013-0098
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analysis of an industrial strain ofStreptomyces bingchenggensisby genome sequencing and gene microarray

Abstract: Streptomyces bingchenggensis is a soil bacterium that produces milbemycins, a family of macrolide antibiotics that are commercially important in crop protection and veterinary medicine. In addition, S. bingchenggensis produces many other natural products including the polyether nanchangmycin and novel cyclic pentapeptides. To identify the gene clusters involved in the biosynthesis of these compounds, and better clarify the biochemical pathways of these gene clusters, the whole genome of S. bingchenggensis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…The loading module of avermectin PKS possesses broad substrate specificity, for example, it can use 2-methylbutyryl-CoA, isobutyryl-CoA and cyclohexylcarbonyl-CoA as substrates to biosynthesize avermectin “a” components, avermectin “b” components and doramectin, respectively [ 2 , 34 ]. However, the loading module of milbemycin in S. bingchenggensis seems to only use acetyl-CoA and propionyl-CoA as substrates to biosynthesize 25-methyl and 25-ethyl milbemycins, respectively [ 15 ]. Therefore, it was speculated that the loading module of avermectin PKS possesses a broader substrate specificity than that of milbemycin PKS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loading module of avermectin PKS possesses broad substrate specificity, for example, it can use 2-methylbutyryl-CoA, isobutyryl-CoA and cyclohexylcarbonyl-CoA as substrates to biosynthesize avermectin “a” components, avermectin “b” components and doramectin, respectively [ 2 , 34 ]. However, the loading module of milbemycin in S. bingchenggensis seems to only use acetyl-CoA and propionyl-CoA as substrates to biosynthesize 25-methyl and 25-ethyl milbemycins, respectively [ 15 ]. Therefore, it was speculated that the loading module of avermectin PKS possesses a broader substrate specificity than that of milbemycin PKS.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent inactivation of the gene encoding a C5-ketoreductase led to the accumulation of 5-oxomilbemycins A3/A4, which can be used as the substrate for the semi-synthesis of milbemycin oxime through one step chemical reaction [ 7 ]. The milbemycin biosynthetic gene cluster mil in S. bingchenggensis consists of four large ORFs ( milA1 – milA4 ) encoding giant multifunctional polypeptides of PKS, some regulatory genes and genes encoding tailoring enzymes (Additional file 1 : Figure S1), which are highly homologous to avermectin biosynthetic gene cluster ave [ 15 ]. Both milbemycin and avermectin PKSs consist of 12 modules, each of which contains distinctive active site domains catalyzing a specific round of polyketide chain elongation.…”
Section: Introductionmentioning
confidence: 99%
“…The probes containing the upstream regions of the 72 genes were amplified (Supplementary Table S1 ). Subsequent EMSAs showed that SbbR has strong affinity for 11 DNA probes ( Figure 8 ), and the deduced products of the putative target genes were as follows: two SARP family CSRs (SBI_08420 and SBI_08432) of nanchangmycin biosynthetic gene cluster ( Wang et al, 2013 ), one SARP family CSR (SBI_09158) of actagardine biosynthetic gene cluster ( Wang et al, 2013 ), one LAL family CSR (SBI_00827) of a cluster encoding non-ribosomal peptide synthases ( Wang et al, 2013 ), one LAL family CSR (SBI_01376) of lasalocid biosynthetic gene cluster ( Wang et al, 2013 ), one putative LAL family regulator (SBI_09325) of melanin biosynthetic gene cluster ( Wang et al, 2013 ), one putative Sig24 homologous regulator (SBI_06451, Sig24 sbh ) of desferrioxamine biosynthetic gene cluster ( Wang et al, 2013 ), one GlnR homolog (SBI_05051, GlnR sbh ), one WblA-like protein (SBI_05811, WblA sbh ), one AtrA homolog protein (SBI_05779, AtrA sbh ), and one MtrA/B-type two-component system (TCS: SBI_06494/06495, MtrA/B sbh ).…”
Section: Resultsmentioning
confidence: 99%
“…A obtenção do DNA plasmidial de E. coli em pequena escala foi realizada pelo método de lise alcalina descrito por Sambrook et al (1989). BENTLEY et al, 2002;HUANG et al, 1998;OMURA et al, 2001;YANG et al, 2013 (BENTLEY et al, 2002;HUANG et al, 1998 (BENTLEY et al, 2002;IKEDA et al, 2003;WANG et al, 2013;ZABURANNYI et al, 2014), onde o metabolismo secundário representa uma porção significativa do genoma e os genes envolvidos com a produção de enzimas para síntese de NRPS e PKS são ubíquos. (BENTLEY et al, 2002;IKEDA et al, 2003;WANG et al, 2013;ZABURANNYI et al, 2014;ZHOU et al, 2012).…”
Section: Extração De Dna Totalunclassified
“…mining" e descrição dos clusters biossintéticos achados no genoma de S. olindensis DAUFPE 5622 (BENTLEY et al, 2002;WANG et al, 2013;ZABURANNYI et al, 2014 NRPS-PKSI Desconhecido…”
Section: Identificação Do Potencial Biotecnológico Utilizando a Abordunclassified